Living through the Great Chinese Famine: Early-life experiences and managerial decisions - Feng, Xunan; Johansson, Anders C. (Journal of Corporate Finance, 2018)
Previous studies have linked personal characteristics of business leaders to corporate decisions and outcomes. We analyze if the traumatic experience of the Chinese Famine has an impact on managerial decisions. By exploiting the exogenous variation in local severity of the famine, we find that having lived through the famine during one's younger years is associated with more conservative financial, investment, and cash holding policies, a lower likelihood of unethical behavior, and better firm performance during economic downturns.